(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical-methodological foundations of the development of differentiated physical education of junior grade students, the parameters of the development of differentiated physical education of junior grade students based on the cluster approach are studied. Pedagogical foundations of the development of differentiated physical education of junior high school students are also analyzed.